Large-eddy simulation for solid particle transport and deposition in a helically rib-roughened pipe using an Euler-Lagrange approach. (18th May 2022) - Akermann, Kevin; Renze, Peter; Schröder, Wolfgang
Highlights: Multiphase LES of particle-laden turbulent flow in a multiple-started helically rib-roughened pipe. Validation of the Euler–Lagrange approach with literature data. An adhesion and removal model are added to consider rebound and removal of the particles. Numerical investigations of the transport and the deposition of solid particles. Deposition rates and velocities for various particle diameters and different Reynolds numbers are presented. Abstract: Multiphase large-eddy simulations of a particle-laden turbulent flow in a helically rib-roughened pipe were performed for Re = 10000, 16000, and 20000 by using an Euler–Lagrange approach. Cyclic boundary conditions were imposed to the continuous as well as the dispersed phase, to get a fully developed particle-laden turbulent flow and a constant deposition rate N ̇ d of the solid particles. The validation of the computation of the turbulent continuous and the disperse phase by the cyclic Euler–Lagrange approach, as well as the deposition of the particles, is based on particle-laden backward-facing step and cyclic duct flow simulations. An adhesion model, dependent on a critical particle velocity u p, crit, and a removal model, dependent on a critical wall-shear stress τ w, crit, were added to the ribbed pipe flow simulations to take the physical effect of particle rebound and particle removal into account. Simulation results of deposition rates N ̇ d and deposition velocities u d + for a variety of particle diameters D p and model parameters are investigated. The simulations showed that significantly less particle adhere to the wall when taking into account the adhesion and removal model. A self-cleaning effect of the almost entire pipe wall at specific particle diameters D p or particle relaxation times τ p + due to wall-shear stress removal could be found as well as a limit value from which the effect of this kind of removal is reduced.